KOMPETENSI TINDAK DIREKTIF ANAK USIA PRASEKOLAH - Eti Stiawati (Fakultas Sastra Universitas Negeri Malang, 2012)
This study aims to assess the competence of preschool children in conducting directive act. The data gathered were in the form of utterances that contained forms, functions, and strategies in conducting directive act. The subjects of this study were children aged 3; 0-5; 0 years from educated families. The theories used were the pragmatic theory and the Ethnography of Communication. The data were analyzed using an interactive model. The results of the study showed that preschool children are already using (1) fourteen competences of directive acts, (2) six competencies of directive act functions; and (3) strategic competence of directive acts done directly and indirectly